Monolayer Quantum-Dot Based Light-Sensor by a Photo-Electrochemical Mechanism - Nanda, Sitansu Sekhar; Kim, Minjik; Yoo, Sung Jong; Papaefthymiou, Georgia C.; Yi, Dong Kee (MDPI, 2020)
Monolayer nanocrystal-based light sensors with cadmium-selenium thin film electrodes have been investigated using electrochemical cyclic voltammetry tests. An indium tin oxide electrode system, with a monolayer of homogeneously deposited cadmium-selenium quantum dots was proven to work as a photo-sensor via an electrochemical cell mechanism; it was possible to tune current densities under light illumination. Electrochemical tests on a quantum dot capacitor, using different sized (red, yellow and green) cadmium-selenium quantum dots on indium tin oxide substrates, showed typical capacitive behavior of cyclic voltammetry curves in 2M H2SO4 aqueous solutions. This arrangement provides a beneficial effect in, both, charge separation and light sensory characteristics. Importantly, the photocurrent density depended on quantum yield rendering tunable photo-sensing properties.